Actividades físico-recreativas para reducir el comportamiento agresivo en los niños de quinto y sexto año de la escuela de educación básica municipal Tierras Coloradas de la ciudad de Loja período marzo – julio 2015 - Elizalde Rojas, Cinthia Lissbeth (2016)
The present thesis entitled: PHYSICAL-RECREATIONAL ACTIVITIES TO REDUCE AGGRESSIVE BEHAVIOR IN CHILDREN FROM FIFTH AND SIXTH YEAR AT MUNICIPAL SCHOOL OF BASIC EDUCATION “TIERRAS COLORADAS” IN LOJA CITY, ACADEMIC YEAR MARCH-JULY 2015 emerges as a strategy to solve the problem encountered in this population regarding to physical, verbal and gestural aggressive behavior, making it difficult for these children to interact appropriately in the social field and also in their daily activities. Faced with this situation, it has arisen as a general objective to reduce aggressive behavior through physical-recreational activities in children from fifth and sixth year at Municipal School of Basic Education "Tierras Coloradas" in Loja city, academic period March-July 2015, through a workshop of physical-recreational activities. The present work is framed in the action research, through the intervention; the type of study was descriptive, correlational and explanatory, the approach is of mixed character that is quantitative-qualitative, the methods that were applied in the research were framed in three areas: theoretical-diagnostic, design and planning of the alternative, and assessment and valuation of the effectiveness of the alternative, the instrument applied to the diagnosis was an observation guide to the children from the institution. The population was 46 children between boys and girls; the judgment of the sample was not probabilistic, since it was the instrument that gave the results of aggressive behaviors evidenced in 16 boys and girls. From the results obtained by applying the observation guide, it is concluded that it was achieved to reduce aggressive behavior in a great sample of the population; therefore it is suggested the continuity in the application of this proposal of change.